Quickly Proving Diestel's Normal Spanning Tree Criterion - Pitz, Max (The Electronic Journal of Combinatorics, 2021)
We present two short proofs for Diestel's criterion that a connected graph has a normal spanning tree provided it contains no subdivision of a countable clique in which every edge has been replaced by uncountably many parallel edges.